Hubungan antara Perceived Social Support dan School Burnout dengan Student Engagement pada Siswa-Siswi SMP X - Firdaus, Nur Azizah Fitriani; Fikri, Aldinel (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
Student engagement is an important indicator of educational effectiveness that plays a role in developing discipline, responsibility, and social skills. Student engagement can also increase learning motivation and emotional well-being, as well as encourage critical thinking and problem-solving skills. Students with high engagement tend to be better prepared to face life's challenges and achieve academic success in the future. This study was conducted to analyse the relationship and contribution of the variables perceived social support and school burnout to student engagement among students at SMP X. The study employed two quantitative research methods: Pearson product-moment correlation analysis and multiple linear regression analysis. The instruments used in this study include: The Multidimensional Scale of Perceived Social Support (MSPSS), School Burnout Inventory (SBI), and Student Engagement Scale (SES). This study involved 495 students, with the analysis results showing a positive relationship between perceived social support and student engagement (r = 0.538, p 0.05), while school burnout had a negative relationship with student engagement (r = -0.303, p 0.05). Meanwhile, regression analysis showed that both variables simultaneously contributed 34.5% to student engagement (R2 = 0.345), while the remaining 65.5% was attributed to other factors. Overall, perceived social support and school burnout were found to significantly contribute to student engagement. The level of perceived social support and the level of burnout experienced by students at school mutually influence and play a role in determining the extent to which students actively participate in academic and non-academic activities in the school environment.ABSTRAKKeterlibatan siswa merupakan indikator penting dari efektivitas pendidikan yang berperan dalam mengembangkan disiplin, tanggung jawab, dan keterampilan sosial. Keterlibatan siswa juga dapat meningkatkan motivasi belajar dan kesejahteraan emosional, serta mendorong kemampuan berpikir kritis dan pemecahan masalah. Siswa yang memiliki keterlibatan tinggi, cenderung lebih siap dalam menghadapi tantangan hidup dan mencapai keberhasilan akademik di masa depan. Penelitian ini dilakukan untuk menganalisis keterkaitan serta kontribusi variabel perceived social support dan school burnout terhadap student engagement pada siswa siswi SMP X. Penelitian menggunakan dua metode penelitian kuantitatif yaitu teknik analisis korelasi pearson product moment dan analisis regresi linear berganda. Instrumen yang digunakan dalam penelitian ini meliputi: The Multidimensional Scale of Perceived Social Support (MSPSS), School Burnout Inventory (SBI), dan Student Engagement Scale (SES). Penelitian ini melibatkan 495 siswa, dengan hasil analisis menunjukkan adanya hubungan positif antara perceived social support dengan student engagement (r = 0.538, p 0.05), sedangkan school burnout memiliki hubungan negatif dengan student engagement (r = -0.303, p 0.05). Sementara itu, analisis regresi menunjukkan bahwa kedua variabel secara simultan berkontribusi sebesar 34,5% terhadap keterlibatan siswa (R2 = 0.345), sementara 65,5% sisanya disebabkan oleh faktor lain. Secara keseluruhan, perceived social support dan school burnout terbukti secara signifikan berkontribusi terhadap student engagement. Tingkat dukungan sosial yang dirasakan serta tingkat burnout yang dialami oleh siswa di sekolah, saling berpengaruh dan berperan dalam menentukan sejauh mana siswa berpartisipasi secara aktif dalam aktivitas akademik dan non-akademik di lingkungan sekolah.